DIAGNOSIS KESULITAN BELAJAR SISWA DALAM PEMBELAJARAN AKTIF DI SEKOLAH - Ismail Darimi (Jurnal Edukasi : Jurnal Bimbingan Konseling, 2016)
Lazy and helpless, indifferent and standing against teachers is part of the learning problems of students. The problem tendency not all students can complete in itself. Teachers contribute to help solve the problems faced by students, the teacher's role is needed by learners, the diagnosis aims to determine where lies the learning difficulties faced by the students as well as to find solutions. If the students' learning difficulties is allowed, then the learning objectives will not be achieved well. To overcome these difficulties, the students need help, both in digesting the teaching materials as well as in overcoming other barriers. Students' learning difficulties should be identified and can be addressed as early as possible, so that the instructional goals can be achieved with good. It is necessary to diagnosis of the implementation of this diagnosis helps students to acquire maximum learning results. To conduct the diagnosis of learning difficulties must be taken several phases of activities such as 1) Identify students who are expected to have learning difficulties; 2) localizes learning difficulties; 3) Determine the factors that cause learning difficulties; 4) Estimate of alternative aid; 5) Establish the possibility of how to overcome them; and 6) Follow-up. The diagnosis of learning difficulties do with the testing techniques and nontes. The technique can be used by teachers to diagnose learning difficulties, among others: the test requirements (prerequisite knowledge, skill prerequisites), diagnostic tests, interviews and observations.